Pengaruh Kebijakan Hutang Jangka Panjang Terhadap Kinerja Keuangan Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2019 - Sari, Deni Laila; Mazni, Afdal (Jurnal Manajemen DIVERSIFIKASI, 2022)
This study aims to test whether long-term debt and total debt affect the financial performance of publicly traded companies listed on the Indonesia Stock Exchange in 2019 as measured by Return On Equity. This type of research is quantitative research with the data used is data in the form of numbers. which was compiled based on existing sources in the financial statements of property and real estate companies listed on the Indonesia Stock Exchange in 2018-2019. Research data analysis was carried out using quantitative data analysis by testing instrument requirements, analysis requirements and hypotheses. The results showed that simultaneously Long Term Debt, Total Debt did not have a significant effect on Return On Equity in Go Public Sector and Real Estate Companies listed on the Indonesia Stock Exchange for the 2018-2019 period. Keyword: Long Term Debt Policy, Financial Performance